Literasi matematis dan mathematical habits of mind peserta didik dalam menyelesaikan soal matematika berorientasi kemampuan 4C - Rahmawati, Imma Rokhima; Apariyani, Dwi Cahyane Nur; Susanto, Hari Purnomo (Jurnal Edumatic: Jurnal Pendidikan Matematika, 2024)
This study aims to determine the mathematical habits of students and students' mathematical literacy skills in solving 4c ability-oriented math problems. This research was a descriptive research with a qualitative approach. Data collection techniques were questionnaires, tests, and interviews. The sample of this research was eight grade students of MTs Negeri 1 Pacitan in academic year of 2021/2022. The total samples were 32 students by using purposive sampling technique. The instrument that used in this research were a mathematical habits of mind's questionnaire and 4c ability-oriented mathematical literacy test. The data analysis technique used the Miles and Huberman model. The results of this study indicate that students of MTs Negeri 1 Pacitan produce data, namely 31% of students have high mathematical habits of mind, 31% of students have average mathematical habits of mind and 38% of students have low mathematical habits of mind, then the total number of participants in the low category was higher than in the high and medium categories. Based on the analysis of the results of the answers and interviews, it can be concluded that one sentence has not accomplished by the students were mathematical literacy to interpret the situation mathematically, the use of variables, and symbols, mathematical concepts, facts, procedures, and the reason in answering questions correctly. At low Mathematical habits of mind students were able to use communication skills and collaboration skills. Sstudents with average and high mathematical habits of mind were able to use critical thinking skills, mathematical communication skills and collaboration skills